Myeloid Cell Function in MRP-14 (S100A9) Null Mice - Hobbs, Josie A. R. (American Society for Microbiology, 2003)
Myeloid-related protein 14 (MRP-14) and its heterodimeric partner, MRP-8, are cytosolic calcium-binding proteins, highly expressed in neutrophils and monocytes. To understand the function of MRP-14, we performed targeted disruption of the MRP-14 gene in mice. MRP-14(−/−) mice showed no obvious phenotype and were fertile. MRP-8 mRNA but not protein is present in the myeloid cells of these mice, suggesting that the stability of MRP-8 protein is dependent on MRP-14 expression. A compensatory increase in other proteins was not detected in cells lacking MRP-8 and MRP-14. Although the morphology of MRP-14(−/−) myeloid cells was not altered, they were significantly less dense. When Ca(2+) responses were investigated, there was no change in the maximal response to the chemokine MIP-2. At lower concentrations, however, there was reduced responsiveness in MRP-14(−/−) compared with MRP-14(+/+) neutrophils. This alteration in the ability to flux Ca(2+) did not impair the ability of the MRP-14(−/−) neutrophils to respond chemotactically to MIP-2. In addition, the myeloid cell functions of phagocytosis, superoxide burst, and apoptosis were unaffected in MRP-14(−/−) cells. In an in vivo model of peritonitis, MRP-14(−/−) mice showed no difference from wild-type mice in induced inflammatory response. The data indicate that MRP-14 and MRP-8 are dispensable for many myeloid cell functions.